Production Cost Control Through Variance Analysis: Evidence from PT Kalimantan Concrete Engineering Indonesia - Risha Zuraida; Noor Safrina; Rizky Amelia; Hikmahwati; Julkawait; Mark Gabriel Wagan Aguilar (P3M Politeknik Negeri Banjarmasin, 2025)
This study aims to identify and analyze the production cost budget as a control tool used to manage production costs at PT Kalimantan Concrete Engineering Banjarmasin by comparing the company’s budgeted production costs with actual production costs at the end of the period and conducting variance analysis on the deviations. This research employs a quantitative research approach. The data used in this study consist of production cost data from the company’s work plan and budget, as well as their realizations. Data collection techniques included direct case study field observations and literature review. The data analysis method applied in this study is descriptive analysis, which comprehensively describes the data obtained during the research process. The calculation methods used include variance analysis of direct material costs, direct labor cost variances (variance one, variance two, and variance three), and factory overhead cost variance (variance one). The conceptual framework of this study focuses on production cost budgeting, production costs, variance analysis, and deviation analysis (variance analysis) of direct material costs, direct labor costs, and factory overhead costs. The results of this study indicate that the production cost budget used as a production cost control tool at PT Kalimantan Concrete Engineering has not functioned optimally, as unfavorable variances are still observed. The overall cost variance in 2022 was favorable, amounting to Rp 25,782,095,189, while the overall cost variance in 2023 was unfavorable, amounting to Rp 9,383,538,032.